2021
DOI: 10.1186/s41927-021-00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of an internet-based pain coping skills training program for patients with systemic Lupus Erythematosus

Abstract: Background Patients with Systemic Lupus Erythematosus (SLE) often experience pain and other symptoms that negatively impact quality of life. Interventions that enhance the use of behavioral and cognitive coping strategies may lead to improved outcomes among patients with SLE. Pain coping skills training (PCST) programs have been shown to improve outcomes among patients with other rheumatic conditions, but there have been no trials of PCST among patients with SLE. This study was a preliminary as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Furthermore, an RCT that investigated web-based patient education and counselling14 (LoE: 3; CA: weak) and a quasi-experimental study that examined an educational programme for enhancing self-management in patients with SLE71 (LoE: 3; CA: intermediate) found these interventions to be efficacious in improving self-efficacy. A pilot RCT that investigated an internet-based coping skill training programme in patients with SLE revealed benefit in HRQoL72 (LoE: 3; CA: weak), as did a qualitative study of multidisciplinary patient education52 (LoE: 4; CA: robust).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, an RCT that investigated web-based patient education and counselling14 (LoE: 3; CA: weak) and a quasi-experimental study that examined an educational programme for enhancing self-management in patients with SLE71 (LoE: 3; CA: intermediate) found these interventions to be efficacious in improving self-efficacy. A pilot RCT that investigated an internet-based coping skill training programme in patients with SLE revealed benefit in HRQoL72 (LoE: 3; CA: weak), as did a qualitative study of multidisciplinary patient education52 (LoE: 4; CA: robust).…”
Section: Resultsmentioning
confidence: 98%
“…This updated version demonstrates acceptable face, content, convergent, discriminant and criterion validity with acceptable internal consistency and reliability in all domains, except procreation and coping. LupusPRO has only been used in two clinical trials to date [51,52]. One examined the efficacy of an online training program focused on development of pain-coping skills (PainTRAINER) in SLE Patients and reported meaningful improvements in LupusPRO HRQoL scores in patients who received the intervention compared to those in the wait-list control group at 9 weeks [51].…”
Section: Lupuspromentioning
confidence: 99%
“…LupusPRO has only been used in two clinical trials to date [51,52]. One examined the efficacy of an online training program focused on development of pain-coping skills (PainTRAINER) in SLE Patients and reported meaningful improvements in LupusPRO HRQoL scores in patients who received the intervention compared to those in the wait-list control group at 9 weeks [51]. The other trial demonstrated significant improvements in LupusPRO body image (BI) scores in patients with cutaneous involvement who received a novel BI intervention that used a cognitive-based therapy approach compared to those who did not.…”
Section: Lupuspromentioning
confidence: 99%
See 1 more Smart Citation
“…LupusQoL has been used in three drug-related RCTs, however the collected data were used in PRO exploratory analyses [ 22 , 23 ]. LupusPRO has not been used in RCTs, only pilot studies of health interventions [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%